Improving students' understanding of fraction concepts and arithmetic operations after learning using bingo media - Ariep Mulyadi; Muhajir; Nuril Huda (Rafandha Press, 2026)
Background: Some studies show that maths instruction in fractions in elementary schools still suffers from low conceptual understanding and arithmetic skills of the students. This is because the use of conventional learning methods which do not encourage students to learn also requires media that are more innovative and interactive. Purpose: This study aims to determine the effect of using bingo learning media on students' understanding of concepts and arithmetic operations of fractions. Method: An experimental design with non-equivalent control group design was employed. This research was conducted on an experimental class and a control class, both consisting of 52 students. Multiple-choice and essay were the tests to collect data that subsequently analyzed in independent sample t-test, MANOVA respectively. Findings: The average conceptual understanding of the experimental class was obtained at 87.31, while that of the control class was 58.08 so as to produce a significance value of 0.000; thus, H0 is rejected and Ha is accepted. The ability to operate fractions was also better in the experimental class with an average of 80.96 compared to the control class at 51.15, with a significance value of 0.000. The MANOVA test results showed a significance value of 0.000, which indicated a simultaneous effect. These findings indicate that bingo media is effective in increasing student engagement, strengthening conceptual understanding, and practicing procedural skills in fraction material.